Legal Aspects Of Female Workers At Night Entertainment - Ivan Nadief (International Asia Of Law and Money Laundering (IAML), 2022)
The development of human life that lived in the millennial era and entered the Industrial Revolution resulted in night entertainment such as clubs and Discos is currently increasing in number. It is inevitable that nightclubs play an important role in encouraging several economic sectors in the country. The development of nightlife venues as a promising business has made many female workers involved because female workers can attract more customers to enter nightlife venues. Where it has been regulated in Article 76 of Law Number 13 of 2003 on Labor and human resources for women workers.